(untitled) (Journal of Dhaka National Medical College & Hospital, 2016)
This descriptive type of cross sectional study was conducted in some selected hospitals of Dhaka city among three groups of health care personnel, viz waste generator, waste handlers and supervisory persons with a sample size 725 using structured questionnaire separately for each group to explore the need assessment of hospital waste management in Bangladesh from January 2014 to May 2014. Most of the supervisory persons were male (70.8%) and 57.7% respondents had working experience more than 36 months. 84% of them informed that hospital did not supply color bag or bucket for waste segregation. According to 97.3% respondents, International Biohazards was not labeled before and after transportation of waste. 90.7% said that waste management procedure in the hospital is not environmentally friendly. 88% mentioned that there were no guidelines for safe disposal of waste and no waste management guideline hanged at the waste generation site. 70.7% of the supervisory persons did not know whether there is any legislation applicable for Hospital Waste Management. Out of 325 waste generators, 37% respondents were male. 46.5% of the respondents had working experience more than 72 months. 61.2% of the waste generators use bucket for disposal of waste while 44.9% use dustbin. Only 21.5% use plastic bags and wooden boxes. More than half of the respondents (52.9%) handled waste without gloves, 19.7% used gloves and only 7.4% used spades during handling waste. 78.5% waste generator mentioned that they never identified the site of generation of waste. Almost all the respondents (99.4%) had poor practice level. Almost half of the respondents (waste handlers 146, 44.9%) were belonging to the age group of 30-39 years & 4.6% were less than 20 years of age. 38.5% respondents had educational level up to class V,the rest were those who attendant class VI-X 18.5%, SSC pass 5.5% and illiterate were 37.5%. 87.4% (284) of waste handlers had poor knowledge regarding waste management, types, health hazards, method of collection, transportation, storage and prevention of health hazards. Relation between age and knowledge regarding waste management was statistically significant (p-value=0.01). Attitude towards hospital waste management between male and female was statistically significance (p value=0.002). Level of education also found to be statistically significant (p value=0.000). Relation between waste management knowledge and waste handling practice was also statistically significant (p =0.005). Waste handlers without supervision had poor performance of work (P value= 0.005). Lack of guidelines, hospital waste management policy, non availability of equipments at desired time and amount, recognition, wages, lack of training, poor and inappropriate supervision are responsible for low level of practice of waste management; hence improvement of training and supervision along with job facilities in are necessary to improve waste management situation J. Dhaka National Med. Coll. Hos. 2016; 22 (02): 13-16